EVALUATION OF BIOACTIVE COMPOUNDS IN Pseudarenthemum tunicatum LEAVES USING GAS CHROMATOGRAPHY- MASS SPECTROMETRY - Nuria Chinonyerem AMEACHI; Chinemerem Linda CHIJIOKE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Pseudarenthemum tunicatum belongs to the Acanthaceae family and an aqueous infusion of it is taken as a hematinic and for other medicinal purposes. This work was aimed at identifying compounds in dichloromethane/ methanol (1:1v) and methanol extracts of P. tunicatum leaves using Gas Chromatography Mass Spectrometry analysis. Thirty compounds were identified in dichloromethane/methanol extract while thirty five compounds were identified in the methanol extract. The most abundant compounds in the dichloromethane/methanol extract 21-methyl-17-isocholestane-16-[2- [formylthio]ethyl],methyl-5,9,21-octacosatrienoate, 9,19-Cyclolanostan-3-ol, 24-methylene-, (3β.)and n-Hexadecanoic acid which had relative abundance of 13.51%, 12.72%, 10.66% and 10.20% respectively. The most abundant compounds in the methanol extract were 2,5-Furandione- 3-methyl, 5-Hydroxymethylfurfural, 9-Octadecenoic acid, (E) and n-Hexadecanoic acid which had relative abundance of 14.01%, 13.27%, 12.25% and 11.87% respectively. Tetradecanoic acid (i.e myristic acid) and n-Hexadecanoic acid were the only compounds identified in both extracts. Results indicated that polarity of the solvents used in extraction influenced the relative abundance and type of compound extracted. Dichloromethane/ methanol extracted more of the triterpenoids and sterols while methanol extracted more of the flavonoids, fatty acids and fatty acid esters. Various compounds identified are known to have varying bioactivities such as antimicrobial, anticancer, antioxidant and antisickling. As such, P. tunicatum leaves could be useful in the preparation of neutraceuticals.